Examining Gender Mandates as Representation of Women in Political Speech - Diani Syahputri; Yusni Khairul Amri; Ratna Sari Dewi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Discourse Analysis of Teun A. Van Dijk tries to examine the gender mandate of the heads of political parties led by women in showing the representation of women in fighting for gender. Speech text is basically not just a string of words that is only linguistic, but social. Van Dijk's model is divided into three levels: a) macro structure, b) superstructure, and c) micro structure, which is used to analyze discourse critically. The data source uses You Tube through the text of political party speeches. Qualitative research methodology used to examine messages as gender mandates in speechwomen-led politics. Based on the research on political speeches, it can be concluded: There is a significant difference in the thematic structure between MSP and GN, the dominant theme of MSP's political speech is about the political, economic, and historical role of the party, and cadres are considered as party officials. The thematics of GN's speech criticized social realities, the struggle for gender, emancipation, women's wages, and polygamy. The micro structure in the schematic is compiled and assembled on economic studies, state politics, and political messages, commemorating the Asia-Africa Conference, while GN's speech emphasized women such as: Emancipation of gender equality, feelings of party leaders or the mission of the Party which are both attached to one. Stylistics in the choice of diction are used as expressions that have the power to inspire those who hear, using a stylistic style for PDI-P cadres, of course, it can be lively. Meanwhile, the diction used to highlight the stylistics used by GN is more about gender messages and mandates that attract millennials. The use of rhetorical language style in the micro structure was used by the two political party leaders as the party's mandate and mission.